2011
DOI: 10.1002/app.33685
|View full text |Cite
|
Sign up to set email alerts
|

Crystallization of isotactic polypropylene in the presence of a β‐nucleating agent based on a trisamide of trimesic acid

Abstract: Tris-2,3-dimethyl-hexylamide of trimesic acid (TATA) is an new type of b-nucleating agent for isotactic polypropylene (iPP). The crystallization, melting characteristics, and the supermolecular structure of iPP nucleated with TATA were studied on the samples crystallized under nonisothermal and isothermal conditions. The b-nucleating ability of TATA was rather high even at low concentration. It was established that TATA possessed dual nucleating ability generating samples with mixed (a and b) polymorphic compo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
40
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(46 citation statements)
references
References 73 publications
5
40
1
Order By: Relevance
“…The enthalpies of the α form ( ΔHm,α) and β form (ΔHm, β) were obtained by separating the areas of the α and β melting peaks by a “vertical line” method. The crystallinity values of the α ( X α ) and β forms ( X β ) as well as the β crystalline form content ( K DSC ) were calculated as follows: Xα=ΔHm,α/ΔHm,α0 Xα=ΔHm,α/ΔHm,β0 KDSC(%)=100Xβ/(Xα+Xβ) …”
Section: Methodssupporting
confidence: 86%
“…The enthalpies of the α form ( ΔHm,α) and β form (ΔHm, β) were obtained by separating the areas of the α and β melting peaks by a “vertical line” method. The crystallinity values of the α ( X α ) and β forms ( X β ) as well as the β crystalline form content ( K DSC ) were calculated as follows: Xα=ΔHm,α/ΔHm,α0 Xα=ΔHm,α/ΔHm,β0 KDSC(%)=100Xβ/(Xα+Xβ) …”
Section: Methodssupporting
confidence: 86%
“…Varga et al found for the beta-nucleating agent (N,N 0 ,N 00 -tris(2,3-dimethylcyclohexyl))-1,3,5-benzenetricarboxamide) a concentration-dependent behavior in iPP with a MFR of 0.35 and a maximum amount of beta modification at very low concentrations (around 100 ppm). However, no data regarding the mechanical properties of the beta-nucleated iPP were given [26]. In a previous study, we were able to show that this nucleating agent could be used to effectively increase the toughness of a high-MFR iPP [27].…”
Section: Introductionmentioning
confidence: 97%
“…Among these, the use of β‐NAs is considered as the most efficient and convenient way to prepare β‐phase . There are four categories of β‐NAs: (1) γ quinacridone (permanent Red E3B), (2) dicarboxylic acids and their group IIA salts, (3) aromatic amide compounds and its derivatives, such as N , N ′‐dicyclohexylterephthalamide, N , N ′‐dicyclohexylsuc‐cinamide, and N , N ′‐2,6‐naphthalene dicarboxamide, and (4) rare earth metal complexes . Moreover, an aromatic amide type β‐NA N , N ′‐dicyclohexyl‐2,6‐napthalene‐dicarboxamide (TMB‐5) has been reported as a highly efficient nucleating agent for PP to form β‐phase .…”
Section: Introductionmentioning
confidence: 99%